INTRODUCTION OF AMANG RHANG MANYANG TALE THROUGH PMTOH TO STUDENTS OF JANTHO DISTRICT, ACEH BESAR REGENCY - Susandro, Susandro; Andika, Benni; Sari, Dian Permata (Batoboh, 2019)
Amat Rhang Manyang is a tale of Aceh, precisely in Krueng Raya, Nanggore Aceh Darussalam. As a literary work, especially old prose,  this tale can be a source of theater creation, especially PMTOH oral theater. The problem is, this tale only become a myth or fairy tale for children. Therefore, this activity tries to offer that this tale can be presented in form of a performance, namely PMTOH. The process of creation is carried out in the seminar and workshop. The seminar aims to deliver material based on the analysis of the structural aspects of the tale, so that the students have knowledge of the themes, plot and character of the Amat Rhang Manyang. Meanwhile, the workshop phase aims to train the practical abilities of students in playing the character. The next phase is to show the results the accumulation of seminars and workshops on stage. This activity aimed for the students of Jantho City, Aceh Besar District. Furthermore, this activity should be able to provide an understanding of the importance of local art as an identity that contains the philosophy of life of Aceh people.  On the other side, this activity aims to give the student an awareness that local art has a great opportunity to be explored and participate in preserving and developing folk art, especially the art of tale and oral tradition of PMTOH